Anisodamine Ameliorates Hyperkalemia during Crush Syndrome through Estradiol-Induced Enhancement of Insulin Sensitivity - Yu, Jian-Guang; Fan, Bo-Shi; Guo, Jin-Min; Shen, Yun-Jie; Hu, Ye-Yan; Liu, Xia (Frontiers in Pharmacology, 2019)
Hyperkalemia is a major cause of on-site death in crush syndrome (CS), which is more severe and common in male victims. Anisodamine is a belladonna alkaloid and widely used in China for treatment of shock through activation of α7 nicotinic acetylcholine receptor (α7nAChR). The present work was designed to study the protective effect of anisodamine in CS and the possible role of estradiol involved. Male and ovariectomized female CS mice exhibited lower serum estradiol and insulin sensitivity, and higher potassium compared to the relative female controls at 6 h after decompression. There was no gender difference in on-site mortality in CS mice within 24 h after decompression. Serum estradiol increased with similar values in CS mice of both gender compared to that in normal mice. Anisodamine decreased serum potassium and increased serum estradiol and insulin sensitivity in CS mice, and methyllycaconitine, selective antagonist of α7nAChR, counteracted such effects of anisodamine. Treatment with anisodamine or estradiol increased serum estradiol and insulin sensitivity, decreased serum potassium and on-site mortality, and eliminated the difference in these parameters between CS mice received ovariectomy or its sham operation. Anisodamine could also increase blood pressure in CS rats within 3.5 h after decompression, which could also be attenuated by methyllycaconitine, without influences on heart rate. These results suggest that activation of α7nAChR with anisodamine could decrease serum potassium and on-site mortality in CS through estradiol-induced enhancement of insulin sensitivity.